The Effect of Power, Balance and Coordination on Dropkick Conversion Kicking Skills on Rugby 7's Women Athletes DKI Jakarta - Siti Bainingrum; Hidayat Humaid; Taufik Rihatno (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
This study aims to determine the effect of power, balance and coordination on the accuracy of dropkick conversion in female DKI Jakarta rugby athletes. Population is all members of UNJ rugby and Banteng rugby club. The measurement of the accuracy of the dropkick kick uses a drop kick rum kick test, the power variable uses the Vertical Jump test, the balance variable uses the Bosuball Balance Single Leg test. In coordination component, the researcher modified the Sridadi test instrument to be a drop up in test. The analysis technique uses a path analysis approach at a significance level of 0.05. The conclusion of each research finding shows (1) There is a direct influence between each independent variable: power (X1), Balance (X2), and Coordination (X3), (2) There is a direct effect of each independent variable Power (X1), Balance (X2), and Coordination (X3) have a direct effect on the dropkick conversion kick (Y), (3) There is an Indirect Effect of Power (X1) through coordination (X3) of the dropkick conversion kick (Y). There is an indirect effect of balance (X2) through Coordination (X3) on the dropkick conversion (Y). Thus, kick dropkick conversion can be increased through increased power, balance and coordination.